أهمية منهج ابن تيمية في الجمع بين النقل والعقل لتنسيق العلاقة بين الوحي والعلم الحديث = The significance of Ibn Taymiyya’s method in harmonizing between reason and revelation to regulate the relationship between revelation and modern sciences = Kepentingan manhaj Ibnu Taimiyah dalam mengharmonikan wahyu dan akal bagi mengharmonikan hubungan wahyu dan sains moden - Sobri, Muhammad Asrie; Titeh, Mohd Sharuddin; Nik Abdullah, Nik Md. Saiful Azizi (2024)
Ibn Taymiyyah is one of the great figures in the field of revelation and reason sciences, where he renewed the Salafi approach in facing the theological and philosophical currents, and one of his greatest productions is his book named: Dar’ Ta’aruḍ al-Naql wa al-‘Aql (Warding off the Conflict of Reason and Revelation), where he overruled the universal law on which Speculative Theologians relied in the issue of combining revelation and reason and brought solid assets and rules, through which the status of revelation does not undermined reason and its argument, and stressed the complete agreement between valid revelation and sound reason. In our time, the issue of the relationship between revelation and modern empirical science has become a major subject of discussions and controversies. Several Muslim scholars have used the universal law of the Speculative Theologians to set the principles for this relationship. Still, this work has negatively affected some fundamental issues in Islam through the hermeneutical approach of the Divine texts. This effect motivated Ibn Taymiyyah to overturn this universal law, so it is necessary to consider his method in establishing these principles for the relationship between revelation and science. This research aims to reveal Ibn Taymiyyah's criticisms of the total law and what he built as an alternative to that law and then apply it to find the principles that regulate the relationship between revelation and modern science. The researcher used the Qualitative method by analyzing what Ibn Taymiyyah wrote in his books, especially, Dar’ Ta’aruḍ al-Naql wa al-‘Aql (Warding off the Conflict of Reason and Revelation). The researcher found that what Ibn Taymiyyah did is the best alternative to this issue and through which the conflict between revelation and science can be avoided. This research is useful to researchers and Muslims in general in solving this modern dilemma and contributed to guiding the construction of contemporary Islamic intellectual civilization.